Efficacy and safety of Everolimus and Exemestane in hormone-receptor positive (HR+) human-epidermal-growth-factor negative (HER2−) advanced breast cancer patients: New insights beyond clinical trials. The EVA study. (October 2017) - ,; ,; Alù, M.; Ancona, C.; Andreis, D.; Bajardi, E.; Benedetto, C.; Berardi, R.; Bordin, E.; Butti, C.; Capri, G.; Cicchiello, F.; et al.
Abstract: Background: The BOLERO-2 trial reported efficacy and safety of Everolimus (EVE) and Exemestane (EXE) combination in HR+ advanced breast cancer (ABC) patients. The BALLET trial further evaluated the safety of EVE-EXE in HR+ ABC patients, without reporting efficacy data. Aim of the EVA real-life study was to collect data of efficacy and safety of EVE-EXE combination in the clinical setting, as well as exploring efficacy according to EVE Dose-Intensity (DI) and to previous treatment with Fulvestrant. Patients and methods: This study aimed to describe the outcome of ABC pts treated with EVE-EXE combination in terms of median duration of EVE treatment and ORR in a real-life setting. Results: From July 2013 to December 2015, the EVA study enrolled 404 pts. Median age was 61 years (33–83). Main metastatic sites were: bone (69.1%), soft tissue (34.7%) and viscera (33.2%). Median number of previous treatments was 2 (1–7). 43.3% of the pts had received Fulvestrant. Median exposure to EVE was 31.0 weeks (15.4–58.3) in the whole population. No difference was observed in terms of EVE exposure duration according to DI (p for trend = 0.27) or type of previous treatments (p = 0.33). ORR and Disease Control Rate (DCR) were observed in 31.6% and 60.7% of the patients, respectively, with the lowest ORRs confined in CHT pre-treated patients or in those who received the lowest DI of EVE. Grade 3-4 adverse events (AEs) were reported in 37.9% of the patients. Main AEs were: stomatitis (11.2%), non-infectious pneumonitis - NIP (3.8%), anaemia (3.8%) and fatigue (3.2%). Conclusions: The EVA study provided new insights in the use of EVE-EVE combination in HR+ ABC pts many years after the publication of the pivotal trial. The combination is safe and the best response could be obtained in patients receiving the full dose of EVE and/or after hormone-therapy as Fulvestrant in ABC. Highlights: In this real-life study, median duration of EVE-EXE combination was higher than that reported in the pivotal trial (31.0 vs. 14.6 weeks), with similar incidence of severe adverse events, namely stomatitis (11.2% vs. 8%) and non-infectious pneumonitis (3% vs. 3.8%). Better selection of patients (visceral sites: 33.2% vs. 54%) and an appropriate management of adverse events can lead to a longer disease control. Previous treatment with Fulvestrant doesn't affect the efficacy of EVE-EXE combination; no difference was observed in terms of EVE exposure duration according to Dose Intensity (p for trend = 0.27), even if the lowest ORR was observed in those patients who received a median DI below or equal 5 mg per day. The EVA study provides useful information for the selection of advanced breast cancer patients for whom EVE-EXE can represent a valid treatment option.